Evaluating Training Methods for Transporting Contingency Management to Therapists - Henggeler, Scott W. (2013)
The effects of three increasingly intensive training methods on therapist use, knowledge, and implementation adherence of contingency management (CM) with substance abusing adolescents were evaluated. Ten public sector substance abuse or mental health provider organizations were randomized to one of three training conditions: workshop and resources (WS+), WS+ and computer assisted training (WS+/CAT), or WS+/CAT and supervisory support (WS+/CAT/SS). Across conditions, 161 therapists participated in the training experiences, and measures were obtained at baseline and 2-month intervals for 12 months following workshop participation. Across training conditions, therapists reported increased CM use, knowledge, and implementation adherence through the 12-month follow-up. The findings show that community-based practitioners are amenable to the adoption of evidence-based treatments when provided access to useful resources. Moreover, high quality workshops in combination with resource access can increase knowledge of the evidence-based treatment and might enhance intervention adherence to a level needed to improve youth outcomes.